Who is serving whom? Exploring the mechanisms linking technology dependence to work engagement - Žiedelis, Arūnas; Urbanavičiūtė, Ieva; Lazauskaitė-Zabielskė, Jurgita; Jakštienė, Rita (Frontiers in Psychology, 2025)
As technological advances increasingly shape the world of work, it is becoming clear that the impact of increased employee dependence on technology for task completion may have ambivalent effects. While successfully mastered technological tools make the work more engaging by enabling a simpler and more efficient implementation of tasks, the necessity to keep up with technological progress imposes additional demands to adopt innovations and limits the freedom of choice about how work is performed. With this study, we sought to unravel whether the effect of technology dependence at work on employee autonomy satisfaction and subsequent work engagement is conditional and depends on increased learning demands. A heterogeneous sample of 753 employees participated in the survey. We used conditional process analysis to test our hypotheses. Results revealed that it is not dependence on technology itself that is relevant for autonomy and work engagement, but rather its combination with intensified learning demands. For employees who reported fewer learning pressures, technology dependence was an enabling (i.e., facilitating autonomy satisfaction) factor, associated with higher work engagement. Conversely, for those who experienced greater learning demands, technology dependence was associated with lower autonomy satisfaction and lower work engagement.